Community-based organisations for vulnerable children in South Africa: Reach, psychosocial correlates, and potential mechanisms - Yakubovich, A; Sherr, L; Cluver, L; Skeen, S; Hensels, I; Macedo, A; Tomlinson, M (Elsevier, 2016)
Community-based organizations (CBOs) have the potential to provide high quality services for orphaned and vulnerable children in resource-limited settings. However, evidence is lacking as to whether CBOs are reaching those who are most vulnerable, whether attending these organizations is associated with greater psychosocial wellbeing, and how they might work. This study addressed these three questions using cross-sectional data from 1848 South African children aged 9–13. Data were obtained from the Young Carers and Child Community Care studies, which both investigated child wellbeing in South Africa using standardized self-report measures. Children from the Child Community Care study were all CBO attenders, whereas children from Young Carers were not receiving any CBO services, thereby serving as a comparison group. Multivariable regression analyses were used to test whether children attending CBOs were more deprived on socio-demographic variables (e.g., housing), and whether CBO attendance was in turn associated with better psychosocial outcomes (e.g., child depression). Mediation analysis was conducted to test whether more positive home environments mediated the association between CBO attendance and significantly higher psychological wellbeing. Overall, children attending CBOs did show greater vulnerability on most socio-demographic variables. For example, compared to children not attending any CBO, CBO-attending children tended to live in more crowded households (OR 1.22) and have been exposed to more community violence (OR 2.06). Despite their heightened vulnerability, however, children attending CBOs tended to perform better on psychosocial measures: for instance, showing fewer depressive symptoms (B = − 0.33) and lower odds of experiencing physical (OR 0.07) or emotional abuse (OR 0.22). Indirect effects of CBO attendance on significantly better child psychological wellbeing (lower depressive symptoms) was observed via lower rates of child abuse (B = − 0.07) and domestic conflict/violence (B = − 0.03) and higher rates of parental praise (B = − 0.03). Null associations were observed between CBO attendance and severe psychopathology (e.g., suicidality). These cross-sectional results provide promising evidence regarding the potential success of CBO reach and impact but also highlight areas for improvement.